Evaluation of hormonal and adipokine biomarkers in the diagnosis of polycystic ovary syndrome – a case-control study - Alredha, Redha Dawud Abd; Haddawi, Krarr Haider; Al-Hayali, Wisal Raoof; Yaseen, Bushra Raouf (Rzeszów University Press, 2025)
Introduction and aim. Polycystic ovary syndrome (PCOS) is a prevalent endocrine disorder that significantly affects women of reproductive ages. This study evaluated the diagnostic potential of hormonal biomarkers such as anti-Müllerian hormone (AMH), total and free testosterone, ratio of luteinizing hormone (LH/FSH) ratio, and adipokines, including visfatin and kisspeptin, in distinguishing PCOS patients from healthy controls. Material and methods. In this case-control study, 50 women diagnosed with PCOS were compared with 50 controls of the same age. Demographic and clinical data were collected through structured interviews and physical examinations. Physical activity levels was assessed using the International Physical Activity Questionnaire short form as well as anthropometric measurements were performed using a calibrated digital scale Seca 803. Blood samples were analyzed for AMH, total and free testosterone, LH/FSH ratio, visfatin, and kisspeptin levels using enzyme-linked immunosorbent assay. Results. PCOS patients exhibited significantly higher levels of AMH (8.1±2.3 ng/mL vs. 4.07±1.1 ng/mL, p<0.001), Free testosterone (4.55±0.95 pg/mL vs. 2.47±0.46 pg/mL, p<0.001), visfatin (86.6±11.02 ng/mL vs. 49.53±10.25 ng/mL, p<0.001), and kisspeptin (9.88±1.96 ng/mL vs. 4.84±1.07 ng/mL, p<0.001) compared to controls. Logistic regression showed that elevated levels of AMH (odds ratio [OR]=2.95, p=0.0056), visfatin (OR=1.7, p=0.0043) and kisspeptin (OR=18.3, p=0.0015) were strongly associated with PCOS. Conclusion. These findings confirmed the significant role of AMH, testosterone, visfatin, and kisspeptin in the diagnosis of PCOS. Integration of adipokine markers, particularly visfatin and kisspeptin, with traditional hormonal markers enhances diagnostic accuracy.
Ethical clearance was granted by the Institutional Review Board of the Medical Laboratory Techniques, College of Health and Medical Techniques at Al-Furat Al-Awsat Technical University, Al-Kufa, Iraq (Approval Number: 31003).
Keywords: anti-Müllerian hormone; diagnosis; kisspeptin; LH/FSH ratio; PCOS; testosterone; visfatin